(untitled) (Innovaciones Educativas, 2021)
This article disseminates the results of an evaluative investigation of some aspects of the digital tablet integration program in the classroom, based on the perceptions of a specific secondary education community after four years of implementation. First, the questionnaires addressed to 48 students and 21 families are analyzed quantitatively and with a descriptive design. Then, in a qualitative way, the opinions of three teachers and a member of the Technical Service are described through semi-structured interviews regarding their satisfaction and the suitability of using the tablet as an educational tool. The findings show the acceptance of the educational community towards the digital tablet, while identifying some of the challenges when implementing the teaching-learning process with tablets in education (school computer technology, competition teacher related to digital teaching and learning, paper book withdrawal). It is concluded that the tablet implementation program has been perceived as positive, although there is room for improvement from the point of view of connectivity and the application of a cognitive and collaborative pedagogical model.